THE EFFECT OF TEACHING AUDITORY COHESION ACTIVITY ON STUDENTS LISTENING ABILITY - Marsella, Alifia; Supardi, Iwan; Bunau, Eusabinus (FKIP - Universitas Tanjungpura, 2020)
This research is about the use of Auditory Cohesion Activity to raise students listening ability on advance learner of TEFL. The researcher took sample from Eleventh Grade of SMA SANTUN UNTAN Pontianak in Academic Year 2017-2018. The aim of this research was to find out how effective the use of Auditory Cohesion Activity to raise students listening ability is. In conducting this research, the researcher used a Pre-experimental as the method of the research. This research consisted of 3 phases, namely; pre-test, treatment, and post-test. The researcher provided the material and the media that needed in this research. The English teacher of SMA SANTUN led the students did the test and the treatment. The finding of this research shows that there was an improvement on students listening ability through Auditory Cohesion Activity. The effectiveness of Auditory Cohesion Activity on students listening ability could be seen from students’ activity through the whole auditory cohesion activity phase and students’ test score. It has shown by the result of post-test which was higher than pre-test. Before the treatment was given, the mean score of pre-test was 26.40. After they had been given treatment the mean score of students’ post-test is 46.30. From the data analysis, the result of the effect size computation is 3.8. It is higher than 0.5. It means that the use of auditory cohesion activity gave a significant effect, to increase students listening ability.